Copper Porphyrin as a Stable Cathode for High‐Performance Rechargeable Potassium Organic Batteries. Issue 9 (17th April 2020) - Lv, Shenshen; Yuan, Jingjun; Chen, Zhi; Gao, Ping; Shu, Hongbo; Yang, Xiukang; Liu, Enhui; Tan, Songting; Ruben, Mario; Zhao‐Karger, Zhirong; Fichtner, Maximilian
Abstract: Rechargeable potassium‐ion batteries (KIBs) are promising alternatives to lithium‐ion batteries for large‐scale electrochemical energy‐storage applications because of the abundance and low cost of potassium. However, the development of KIBs is hampered by the lack of stable and high‐capacity cathode materials. Herein, a functionalized porphyrin complex, [5, 15‐bis(ethynyl)‐10, 20‐diphenylporphinato]copper(II) (CuDEPP), was proposed as a new cathode for rechargeable potassium batteries. Spectroscopy and molecular simulation studies were used to show that both PF6 − and K + interact with the porphyrin macrocycle to allow a four‐electron transfer. In addition, the electrochemical polymerization of the ethynyl functional groups in CuDEPP resulted in the self‐stabilization of the cathode, which was highly stable during cycling. This unique charge storage mechanism enabled CuDEPP to provide a capacity of 181 mAh g −1 with an average potential of 2.8 V (vs. K + /K). These findings could open a pathway towards the design of new stable organic electrodes for KIBs. Abstract : Copper complex cathode : A copper porphyrin complex as a stable cathode for potassium‐based rechargeable batteries is presented. The unique charge‐storage mechanism of the porphyrin, which involves a fast multielectron transfer and a self‐stabilization process, enables the electrodes to exhibit a high cycling stability with a high energy and power density.